2005
DOI: 10.1007/s00430-005-0241-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy and immunogenicity of Escherichia coli K13 diphtheria toxoid conjugate against experimental ascending pyelonephritis

Abstract: In the present study, protective efficacy of Escherichia coli capsular antigen, K13, was evaluated in a mouse model of pyelonephritis. Unconjugated capsular polysaccharide failed to provide any protection. However, coupling of K13 to diphtheria toxoid (DT) enhanced its immunogenicity and led to significant production of anticapsular antibodies in mice. Immunization of animals with K13-DT conjugate also caused significant improvement in cell-mediated immune response as indicated by an increase in lymphoblastoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…• Heterogeneity of the proteins of the bacterial membrane Targeting capsule (Kaijser et al, 1983;Roberts et al, 1993;Kumar et al, 2005;Stenutz et al, 2006) • Promising animal model results…”
Section: Vaccinementioning
confidence: 99%
“…• Heterogeneity of the proteins of the bacterial membrane Targeting capsule (Kaijser et al, 1983;Roberts et al, 1993;Kumar et al, 2005;Stenutz et al, 2006) • Promising animal model results…”
Section: Vaccinementioning
confidence: 99%
“…For example, immunization with the type 1 fimbrial adhesin, FimH, conjugated to its periplasmic chaperone, FimC, reduced murine bladder colonization by 99.9%, as well as provided protection in a primate model [14],[15]. Additionally, subunit vaccines based on several other surface-exposed molecules such as P fimbriae (PapDG complex), alpha hemolysin, Dr fimbriae, the salmochelin receptor IroN, and a conjugation of capsule polysaccharide K13 with diphtheria toxoid have been shown to induce at least some immune response in immunized animals [16][20]. However, although much research has focused on the development of a vaccine against UPEC, none are available in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Purified E coli K13 polysaccharide conjugated to bovine serum albumin protected rats from pyelonephritis (299). A different group conjugated E. coli K13 to diphtheria toxoid and found that the vaccine decreased renal bacteria load and disease severity scores in mice after challenge with a K13 UPEC strain (300). A considerable challenge in formulating a vaccine targeting capsule or O antigen, the most exposed component of LPS, is the fact that there is a great heterogeneity of serotypes among E. coli isolates.…”
Section: Uti Vaccinesmentioning
confidence: 99%